Thermally induced hydrosilylation at deuterium-terminated silicon nanoparticles an investigation of the radical chain propagation mechanism - Holm, Jason (Langmuir : the ACS journal of surfaces and colloids, 2009)
Isotopic labeling techniques were employed to study alkene addition to hydrogen- and deuterium-terminated silicon nanoparticles. Deuterium-terminated silicon nanoparticle synthesis is described, as is the characterization of fresh deuterium-terminated particles by transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and in situ Fourier transform infrared spectroscopy (FTIR). Particles were refluxed in pure 1-dodecene and subsequently characterized by FTIR and nuclear magnetic resonance (NMR) spectroscopy. (1)H NMR results showed features consistent with dodecyl-terminated nanoparticles. Infrared absorption spectra of refluxed particles showed strong evidence of new C-D bond formation, which is consistent with a radical chain mechanism for alkene addition by hydrosilylation